La producción agrícola y las exportaciones agroindustriales de la Región Loreto periodo 2015 – 2019 - Acuña Soto, Elsa Janeth (2022)
The Loreto region produces a series of agricultural products with unique properties and that is demanded by the international market, being a limitation the reduced exportable offer that it presents. The objective of this research is to determine the relationship between agricultural production and agro-industrial exports of the Loreto region, in the period 2015 - 2019. In line with this objective, the present Quantitative type, Correlational level and nonexperimental design. The investigation concludes that there is no relationship between agricultural production and agro-industrial exports of the Loreto region during the period 2015 - 2019, conclusion based on the result of the Correlation Coefficient that was r = -0.258243902; and the Coefficient of Determination R2 = 0.066689913; results that demonstrate the non-existence of statistical association and determination between the aforementioned variables. Likewise, the main agro-industrial products exported by the region are: Cocoa Beans (30.94%), Prepared or Preserved Hearts of Palm (23.04%) and Coffee Beans (23.02%). The main destination markets for Loreto's agro- industrial exports are: Argentina (18.58%), United States (14.17%) and Malaysia (11.52%). On the other hand, the region's agricultural production showed a growing trend over the five years, having increased at an average annual rate of 1.72%, equivalent to 1,469,945.80 metric tons, part of which went abroad.